Study of Time-Fractional Nonlinear Model Governing Unsteady Flow of Polytropic Gas - Brajesh K. Singh; Haci Mehmet Baskonus; Neetu Singh; Mukesh Gupta; D. G. Prakasha (Axioms, 2023)
The present study is concerned with studying the dynamical behavior of two space-dimensional nonlinear time-fractional models governing the unsteady-flow of polytropic-gas (in brief, pGas) that occurred in cosmology and astronomy. For this purpose, two efficient hybrid methods so-called optimal homotopy analysis <semantics>J</semantics>-transform method (<semantics>O</semantics>HA<semantics>J</semantics>TM) and <semantics>J</semantics>-variational iteration transform method (<semantics>J</semantics>-VITM) have been adopted. The OHA<semantics>J</semantics>TM is the hybrid method, where optimal-homotopy analysis method (<semantics>O</semantics>HAM) is utilized after implementing the properties of <semantics>J</semantics>-transform (<semantics>J</semantics>T), and in <semantics>J</semantics>-VITM is the <semantics>J</semantics>-transform-based variational iteration method. Banach’s fixed point approach is adopted to analyze the convergence of these methods. It is demonstrated that <semantics>J</semantics>-VITM is <semantics>T</semantics>-stable, and the evaluated dynamics of pGas are described in terms of Mittag–Leffler functions. The proposed evaluation confirms that the implemented methods perform better for the referred model equation of pGas. In addition, for a given iteration, the proposed behavior via <semantics>O</semantics>HA<semantics>J</semantics>TM performs better in producing more accurate behavior in comparison to <semantics>J</semantics>-VITM and the methods introduced recently.